2022
DOI: 10.3390/nu14112241
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective and Antiaging Effects of a Standardized Red Orange (Citrus sinensis (L.) Osbeck) Extract in Asian and Caucasian Subjects: A Randomized, Double-Blind, Controlled Study

Abstract: The increase in solar ultraviolet radiation (UVR) that reaches the Earth’s surface should make us reflect on the need to develop new approaches in protecting the skin from UVR exposure. The present study aims to evaluate the photoprotective and antiaging efficacy of a red orange extract (100 mg/day) in both Asian and Caucasian subjects. A randomized, double-blind, controlled study was carried out in 110 Asian and Caucasian subjects. Product efficacy was measured as follows: (1) the photoprotective effect was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The antioxidant properties of the test product were demonstrated in previous in vitro and in vivo studies [ 11 , 14 , 32 ]. This study confirmed the well-known antioxidant efficacy of Citrus sinensis .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The antioxidant properties of the test product were demonstrated in previous in vitro and in vivo studies [ 11 , 14 , 32 ]. This study confirmed the well-known antioxidant efficacy of Citrus sinensis .…”
Section: Discussionmentioning
confidence: 85%
“…In previous in vitro studies on human keratinocytes, the extract showed anti-inflammatory efficacy [ 2 ], protection against UVB-induced damage [ 12 ], and antioxidant properties [ 40 ]. These results were confirmed by in vivo studies on humans in which the extract showed to be effective in reducing the oxidative stress in subjects exposed to air pollutants [ 11 ], in protecting the skin from the UVB-induced skin erythema [ 13 , 14 ], and in decreasing the photoaging clinical signs [ 14 , 41 ]. This study investigated the efficacy of a standardized Red Orange Complex extract (ROC TM , Bionap Srl, 95032 Piano Tavola Belpasso, CT, Italy) on elderly subjects, exploring more in detail the antioxidant efficacy and, preliminarily, the effect of the extract on the wellbeing and on the menopause symptoms of both male and female subjects, respectively.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Based on our previous clinical study results, 100 mg/day of ROC was defined as the effective anti-photoaging dosage. This was converted to a mice dose of 20, 40, or 80 mg/kg by the human equivalent dose [ 17 21 ]. Changes in BW and serum clinical parameters were measured to determine the toxicity of ROC ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, red orange complex H extract (ROC) was administered to examine its protective effect against UVA-B-induced damage and was found to increase the scavenger activity, UVB protection, and anti-inflammatory properties by activating tumor necrosis factor (TNF)-α, interleukin (IL)-6, and NF-κB, and downregulating matrix metalloproteinases (MMPs) content in vitro [ 16 ]. Furthermore, the results of several clinical studies have evidenced that ROC exerts photoprotective and anti-aging effects [ 17 ].…”
Section: Introductionmentioning
confidence: 99%